ANALISIS FAKTOR FAKTOR KEPUASAN TERHADAP LOYALITAS PELANGGAN KARTU FLEXI TRENDY DI KOTA PEKANBARU (Jurnal Tepak Manajemen Bisnis, 2014)
Mobile phone card business is a business in the field of communication services, where the customer isa key in the field. This study analyzes the factors of satisfaction on customer loyalty of Flexi Trendy in Pekanbarucity. The formulation of the problem is the reduction in market share nationally of Flexi Trendy (prepaid) duringthe last five years may be indicated because of lowering customer loyalty of this card users. Therefore, this studyaimed to examine whether the variables of satisfaction that the product quality, relationship value and price ,product features (product feature) ,reliability, Guarantee, response and problem solving , employee experience, and the ease and comfort of an effect on loyalty . The samples are users of Flexi Trendy card ( prepaid ) amountedto 100 people and is located in Plasa Telkom Pekanbaru. The samples in this study is not random ( non -probability sampling ) and analysis tool used is multiple linear regression by using SPSS.17.The results showed that there is positive and significant, both individually and together (simultaneously) betweenproduct quality, relationship value and price, product features (product feature), reliability, guarantee, responseand problem solving, employee experience, and ease of and comfort to loyalty. And variable relationship betweenvalue and price have the most powerful influence in creating customer loyalty Flexi Trendy. Thus the results ofthis study support the all nine hypothesis that have been proposed in this study.Based on the managerial implications of this study can be taken to increase customer loyalty is to improve thequality of products such as signal quality, internet access, increasing the number of BTS stations in order toreach a wider and also improves service quality by conducting training for workers in order to know thestandard of service properly and have to give a clear warranty to customers. Agenda for future research isneeded to add another variable that affects loyalty and increase the number of samples with a broader scope.Keywords: Customer satisfaction, employee experince and convenience, loyalty, relationship value and price